2009
DOI: 10.1002/smll.200900563
|View full text |Cite
|
Sign up to set email alerts
|

Control of the in vivo Biodistribution of Hybrid Nanoparticles with Different Poly(ethylene glycol) Coatings

Abstract: Fluorescent nanoparticles containing a gadolinium oxide core are very attractive because they are able to combine both imaging (fluorescence imaging, magnetic resonance imaging) and therapy (X-ray therapy and neutron-capture therapy) techniques. The exploitation of these multifunctional particles for in vivo applications requires accurate control of their biodistribution. The postfunctionalization of these particles by four different poly(ethylene glycol) derivatives, which differ by chain length and end group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
103
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 30 publications
3
103
0
1
Order By: Relevance
“…Similarly, PEGylation of magnetic gadolinium oxide coated in a fluorescent silane shell has also been reported. [99] A comparison of four different PEGs PEG 250 -COOH, PEG 2000 -COOH, PEG 2000 -OCH 3 , and PEG 2000 -NH 2 showed that the gadolinium oxide coated with methoxy terminated PEG 2000 demonstrated the longest blood circulation time and greatest accumulation in tumor. Changing the methoxy group to amine or carboxy functionality resulted in an increased accumulation of NPs in the liver and spleen as a result of the higher surface charge in these compounds.…”
Section: Pegylation Of Iron Oxide Using Silane Chemistrymentioning
confidence: 99%
“…Similarly, PEGylation of magnetic gadolinium oxide coated in a fluorescent silane shell has also been reported. [99] A comparison of four different PEGs PEG 250 -COOH, PEG 2000 -COOH, PEG 2000 -OCH 3 , and PEG 2000 -NH 2 showed that the gadolinium oxide coated with methoxy terminated PEG 2000 demonstrated the longest blood circulation time and greatest accumulation in tumor. Changing the methoxy group to amine or carboxy functionality resulted in an increased accumulation of NPs in the liver and spleen as a result of the higher surface charge in these compounds.…”
Section: Pegylation Of Iron Oxide Using Silane Chemistrymentioning
confidence: 99%
“…6,56 Particles with varying corona layers throughout the sample and particularly particles with a large number of layers may see effects in affinity, 6 functionality, 6,57 and steric hindrance. 58,59 Therefore, we establish a method to use PSD measurements to estimate the variation in the protein layering within the sample. In a set of images, each interrogation area exhibits a different diffusion coefficient value.…”
Section: E Comparing Psd With Theoretical Predictionsmentioning
confidence: 99%
“…From the fit of a Gaussian function to the histogram, the average diameter of the particles was determined to 3.6 ± 0.9 nm. The size distribution is narrow, and the sizes of the obtained nanoparticles appear small enough to be considered for in vivo MRI applications [19].…”
mentioning
confidence: 99%